Pengaruh Keterampilan, Pemanfaatan Teknologi Informasi, Dan Tingkat Pendidikan Terhadap Kinerja Pegawai (Pada Perusahaan Daerah Air Minum (PDAM) Kota Malang) - Vimilya Artika Sari; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine how the effect of skills, the use of information technology, and the level of education on employee performance at PDAM Malang City. The sampling technique used purposive sampling, the data sample obtained were 77 employees. The method of collecting data using a questionnaire method. The data analysis technique used in this study is multiple linear regression. The results showed that the variable human resource skills had a positive and significant effect on employee performance. The use of information technology has a positive and significant effect on employee performance. The level of education has a positive and significant effect on employee performance. Taken together, the variables of skills, the use of information technology, and the level of education have a positive and significant effect on employee performance. Keywords: Skills, utilization of information technology, level of education, employee performance